Enhanced SARS-CoV-2 entry via UPR-dependent AMPK-related kinase NUAK2 - Prasad, Vibhu; Cerikan, Berati; Stahl, Yannick; Kopp, Katja; Magg, Vera; Acosta-Rivero, Nelson; Kim, Heeyoung; Klein, Katja; Funaya, Charlotta; Haselmann, Uta; Cortese, Mirko; Heigwer, Florian; et al. (Molecular cell, 2023)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) remodels the endoplasmic reticulum (ER) to form replication organelles, leading to ER stress and unfolded protein response (UPR). However, the role of specific UPR pathways in infection remains unclear. Here, we found that SARS-CoV-2 infection causes marginal activation of signaling sensor IRE1α leading to its phosphorylation, clustering in the form of dense ER-membrane rearrangements with embedded membrane openings, and XBP1 splicing. By investigating the factors regulated by IRE1α-XBP1 during SARS-CoV-2 infection, we identified stress-activated kinase NUAK2 as a novel host-dependency factor for SARS-CoV-2, HCoV-229E, and MERS-CoV entry. Reducing NUAK2 abundance or kinase activity impaired SARS-CoV-2 particle binding and internalization by decreasing cell surface levels of viral receptors and viral trafficking likely by modulating the actin cytoskeleton. IRE1α-dependent NUAK2 levels were elevated in SARS-CoV-2-infected and bystander non-infected cells, promoting viral spread by maintaining ACE2 cell surface levels and facilitating virion binding to bystander cells.